The Expansion of Oil Palm Plantations and Ecological Degradation in Borneo: A Thematic (Maudhu‘i) Exegetical Analysis of Qur’anic Verses on the Environment - Jumrotunisak; Khairil Anwar; Taufik Warman Mahfuzh; Hasna Afaf Zahidah (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The expansion of oil palm plantations in the Borneo region over the past few decades has generated intense debate concerning its ecological impacts, including deforestation, biodiversity loss, forest fires, and land-use change. This article aims to analyze this phenomenon through a thematic (maudhu‘i) exegetical approach to Qur’anic verses related to the environment, particularly the concepts of fasād fī al-arḍ (corruption on earth), the mandate of human vicegerency (amānah al-khilāfah), and the principle of balance (mīzān). This study employs a qualitative library-based research design using thematic exegesis by collecting relevant verses, examining their asbāb al-nuzūl (occasions of revelation) and munāsabah (textual coherence), and analyzing them through the lens of Islamic ecotheology and contemporary literature on ecological crisis. The findings indicate that the Qur’an normatively prohibits all forms of exploitation that result in systemic damage to ecosystems. The concept of fasād encompasses not only moral corruption but also ecological destruction caused by human excess and transgression (isrāf and ṭughyān). In the context of Borneo, oil palm expansion becomes problematic when its practices disregard principles of sustainability, ecological justice, and the ethical responsibility inherent in human vicegerency. Nevertheless, the Qur’an does not categorically reject economic activity; rather, it emphasizes maintaining a balance between resource utilization and environmental preservation. This study contributes to the advancement of Islamic ecotheological discourse by positioning thematic exegesis as a normative framework for assessing natural resource–based development practices. The findings underscore the urgency of integrating Qur’anic ethics into oil palm plantation management policies to ensure alignment with sustainability principles and ecological responsibility.